1970
DOI: 10.1159/000175271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Linoleic Acid on Vitamin E Requirement and Fatty Acid Composition of Erythrocyte Lipids in Rats

Abstract: In order to investigate the effect of an increasing linoleic acid content of the diet on vitamin E requirement, young male rats were divided into 4 groups receiving respectively 0.27, 0.98, 3.57 and 12.98% linoleic acid (from mixtures of coconut oil and tocopherol-free safflower oil) in their diets. Each group was subdivided into 6 groups, receiving increasing amounts of D-α-tocopheryl acetate (2.5–23.5 mg) in their food. Spontaneous haemolysis in vitro was used as a criterion for vitamin E requirement. The am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1972
1972
1983
1983

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…With respect to the small effect of linoleic acid intake on vitamin E re quirement, the results of this experiment on ducklings are in agreement with previous results on rats [1,2]. Sg n d e r g a a r d and D am [41] found no effect of the level of dietary linoleic acid (up to 10 cal% of the diet) on the amount of vitamin E, required for protection against encephalomalacia in chickens.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…With respect to the small effect of linoleic acid intake on vitamin E re quirement, the results of this experiment on ducklings are in agreement with previous results on rats [1,2]. Sg n d e r g a a r d and D am [41] found no effect of the level of dietary linoleic acid (up to 10 cal% of the diet) on the amount of vitamin E, required for protection against encephalomalacia in chickens.…”
Section: Discussionsupporting
confidence: 91%
“…The in vitro haemolysis test may be con-sidercd as a typical example of vitamin E acting as an antioxidant, the degree of haemolysis and, therefore, the vitamin E requirement being dependent upon the sensitivity of the erythrocyte membrane lipids to peroxidation [40], If, however, care is taken that the diets contain sufficient EFA. a wide variation in dietary linoleic acid contents is possible, without causing any appreciable effect on the percentage of arachidonic acid in the erythrocyte fatty acids [2], which is equally true of the linoleic acid intake on vitamin E requirement in the haemolysis test, except for very high doses of vitamin E [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, opposite to the findings in chicks (35), the vitamin E deficiency did not give rise to CNS symptoms in the rat. The term 'deficient' is justified by comparison to the work of Jager (18) and Jager and Houtsmuller (21), as the present diet contained less than 1 mg of vitamin E per kilogram and Jager showed that 5 mg/kg diet was low enough to induce an 80% in vitro haemolysis. Furthermore, the present finding of lowered gain in weight as a result of deficiency in vitamin E would, according to Jager (19), only occur when the dietary content of vitamin E is lower than 1.5 mg/kg food.…”
Section: Discussionmentioning
confidence: 93%